2011
DOI: 10.1073/pnas.1009147108
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and objective learning effects dissociate in space and in time

Abstract: Perceptual learning not only improves sensitivity, but it also changes our subjective experience. However, the question of how these two learning effects relate is largely unexplored. Here we investigate how subjects learn to see initially indiscriminable metacontrast-masked shapes. We find that sensitivity and subjective awareness increase with training. However, sensitivity and subjective awareness dissociate in space: Learning effects on performance are lost when the task is performed at an untrained locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 41 publications
3
57
0
Order By: Relevance
“…Blindsight patients deny any subjective visual experience while successfully performing objective visual tasks (Sahraie et al, 1997;Stoerig and Cowey, 1997;De Gelder et al, 2008). Similar, blindsight-like dissociations (also termed implicit perception) have been documented in healthy individuals (Meeres and Graves, 1990;Kolb and Braun, 1995;Lau and Passingham, 2006;Schwiedrzik et al, 2011). Methodologically, such dissociations impose serious difficulties on the search for the neuronal correlates of subjective visual experience.…”
Section: Introductionmentioning
confidence: 91%
“…Blindsight patients deny any subjective visual experience while successfully performing objective visual tasks (Sahraie et al, 1997;Stoerig and Cowey, 1997;De Gelder et al, 2008). Similar, blindsight-like dissociations (also termed implicit perception) have been documented in healthy individuals (Meeres and Graves, 1990;Kolb and Braun, 1995;Lau and Passingham, 2006;Schwiedrzik et al, 2011). Methodologically, such dissociations impose serious difficulties on the search for the neuronal correlates of subjective visual experience.…”
Section: Introductionmentioning
confidence: 91%
“…Rather, perceptual learning was used as a tool that allowed us to decrease sensory noise in our model. Several previous studies have combined confidence ratings and perceptual learning (Guggenmos, Wilbertz, Hebart, & Sterzer, 2016;Schwiedrzik, Singer, & Melloni, 2011;Solovey et al, 2016;Zizlsperger, Kümmel, & Haarmeier, 2016) but while they found important effects of learning on the overall confidence level, none investigated how training affects metacognitive efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results demonstrate that while metacognitive judgments may indeed be related to consciousness, they cannot generally be used as a direct measure of consciousness (Jachs, Blanco, Grantham---Hill, & Soto, 2015). Indeed, perceptual learning has been argued to increase consciousness (Schwiedrzik et al, 2011) but, as seen here, decreases metacognitive efficiency. We see metacognitive scores as invaluable in constructing and testing models of decision making but remain agnostic about their relationship to constructs such as consciousness and working memory.…”
Section: Cc-by 40 International License Peer-reviewed) Is the Authormentioning
confidence: 99%
“…Consistent with the latter prediction, studies investigating the VPL of simple object properties (e.g., shape) have reported accompanying improvements in measures of metacognition (Bertels, Franco, & Destrebecqz, 2012;Schlagbauer, Muller, Zehetleitner, & Geyer, 2012;Schwiedrzik et al, 2011). However, does the VPL of high-level stimulus properties fail to improve accompanying metacognition?…”
mentioning
confidence: 78%
“…Investigating this issue, two parallel bodies of research have recently emerged. One investigates whether conscious stimulus awareness is necessary for VPL (e.g., Seitz et al, 2009;Watanabe et al, 2001), while the other investigates whether conscious stimulus accessibility can be improved by VPL (e.g., Schwiedrzik, Singer, & Melloni, 2011).…”
mentioning
confidence: 99%